Effect of hypertension on peroxidation processes in the retina and optic nerve in experimental diabetes (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Questions treatment of neurodegenerative diseases of the vision is the most urgent problem of ophthalmology.Рurpose. Study the effect of hypertension on peroxidation processes in the eye tissues in experimental diabetes.Methods. Studies were conducted on 34 rabbits. The experimental animals were divided into four groups: the first group — control group (10 rabbits), the second — an experienced group of animals with diabetes in terms of hypertension (8 rabbits), the third — an experienced group of animals with diabetes (8 rabbits), the fourth — the experimental group animals with hypertension (8 rabbits). In isolated tissues of the retina and optic nerve tissue content determination made malondialdehyde and diene conjugates.Results. When streptozotocin diabetes in animals with experimental hypertension intensity of peroxidation markedly increased compared to experiments in which only induced diabetes.Conclusions. It was established experimentally that the development of hypertension in animals with diabetes mellitus leads to a significant enhancement of peroxidation processes in the nervous tissues, compared to diabetic animals without hypertension. For example, in the retina and optic nerve concentration of intermediate and final products of lipid peroxidation was relatively increased — by 22.9 % and 27.7 %, respectively. This factor is an important pathogenetic link to accelerating the development of neurodegenerative processes in the visual analyzer in diabetes mellitus combined with hypertension.
Keywords: retinas; zrytelnыy nerve; peroksydatsyya; dyabet; hypertension